Nasopharyngeal Microbiota as an early severity biomarker in COVID-19 hospitalised patients. Issue 3 (March 2022) - Ventero, Maria Paz; Moreno-Perez, Oscar; Molina-Pardines, Carmen; Paytuví-Gallart, Andreu; Boix, Vicente; Escribano, Isabel; Galan, Irene; González-delaAleja, Pilar; López-Pérez, Mario; Sánchez-Martínez, Rosario; Merino, Esperanza; Rodríguez, Juan Carlos
Highlights: Lower microbiota diversity is linked to a worse prognosis, and increased likelihood of a fatal outcome. The presence of Selenomonas SPP., Filifactor SPP., Actinobacillus SPP. or Chroococcidiopsis SPP., is associated with a reduced risk of invasive mechanical ventilation being required. The microbiome could be used as a prognostic factor. Summary: This study aimed to analyse the diversity and taxonomic composition of the nasopharyngeal microbiota, to determine its association with COVID-19 clinical outcome. To study the microbiota, we utilized 16S rRNA sequencing of 177 samples that came from a retrospective cohort of COVID-19 hospitalized patients. Raw sequences were processed by QIIME2. The associations between microbiota, invasive mechanical ventilation (IMV), and all-cause mortality were analysed by multiple logistic regression, adjusted for age, gender, and comorbidity. The microbiota α diversity indexes were lower in patients with a fatal outcome, whereas the β diversity analysis showed a significant clustering in these patients. After multivariate adjustment, the presence of Selenomonas spp., Filifactor spp., Actinobacillus spp., or Chroococcidiopsis spp., was associated with a reduction of more than 90% of IMV. Higher diversity and the presence of certain genera in the nasopharyngeal microbiota seem to be early biomarkers of a favourable clinical evolution in hospitalized COVID-19 patients. Graphical abstract: Image, graphical abstract .